Cenários da mudança terapêutica na psicoterapia psicodramática: uma revisão de literatura - Barros, Miriam Lopes de (2020)
Considering the current population demand for psychotherapies of proven transformative character and recognizing this therapy characteristic as inherent to psychodramatic psychotherapy, the present study intended to understand the major elements of change in psychodramatic psychotherapy and also verify the contributions added by research of others therapy approaches to psychodrama in this matter. The interest for this topic came from the clinical practice, in office: the mechanisms of change throughout treatment using psychodramatic methods and the need for clarification of the subject which is made up of so many concepts. The suggested literature review was divided into three stages. In the first and second one searches were conducted on the BVS-Psi Platform (Health Virtual Library -Psychology) integrated to SciELO, on the CAPES journal portal, from 2009 to 2019, and on selected articles published in Qualis/CAPES journals A1, A2, B1 and B2 in Portuguese. The first stage included publications of other therapy approaches, while the second, only psychodrama publications. Considering that there are so much material that has not yet been turned into scientific articles, like master theses and doctoral dissertations, a third stage was added to this review: online search on USP (Universidade de São Paulo) platform for theses and dissertations and on scholar google in Portuguese from 2009 to 2019. The outcomes pointed out a lack in psychodramatic psychotherapy production focused on therapeutic change. However, studies with different focus cited the phenomenon in the course of the work indicating some elements as relevant to change in psychodramatic psychotherapy, namely: Creativity and Spontaneity; Moment; Reafference; Tele and Encounter; Surplus Reality; Catharsis of Integration. Similarities between concepts of Adaptative Efficacy and Spontaneity were observed demonstrating that it would be relevant to conduct researches deepening the integration of those concepts in the assessment of psychotherapeutic processes. It was also verified that there is some approximation between assumptions of Dialogical Self Theory, Narrative Therapy and Psychodrama, suggesting possibilities to new researches to deepen such congruences. This study contributed profound reflections on change in psychotherapy, mainly in psychodrama, considering the epistemological and methodological characteristics of this approach in psychology. Supported by the National Council of Scientific and Technological Development, CNPq